PENGEMBANGAN LITERASI PEMASARAN DIGITAL DENGAN EDUKASI BISNIS SEBAGAI TAMBAHAN PENDAPATAN WARGA SIDOBOGEM - Indira, Irma Indira; Agustinus Salukh; Bagus Setiawan; Dimas Ageng Prianto; Muhammad Rizal Faiz Firmansyah; Uswatun Aisyiah (Politeknik Negeri Sriwijaya, 2024)
Technological developments and increasingly high business competition have forced Micro, Small and Medium Enterprises (MSMEs) to have a good marketing strategy to remain competitive with their competitors. This research was conducted to determine the marketing strategies carried out by MSMEs in facing competition in the digital era. Deep research methods. The results of this research use a qualitative approach. The results show that with the socialization of MSME marketing strategies in this digital era and also practices in making Sari Kacang Hijau Jahe (SAKAHIJA) products they can be directly applied and in terms of price, they apply competitive and competitive prices. In addition, they also have a target market that tends to aiming at a niche market so that their products can be accepted by the market. The application of technology is also more widely used in marketing SAKAHIJA's products through websites and social media to establish good relations and communicate with consumers and audiences.